THE REPRESENTATION OF THE CONCEPT OF MONEY IN THE RUSSIAN AND ENGLISH PROVERBIAL CORPUS - Zalavina, Tatyana; Dyorina, Natalja; Antropova, Ludmila; Astashova, Galina; Savinova, Tatjana; Tulupova, Olga (Revista Inclusiones, 2020)
Modern researchers in linguistics concentrate their research effort on the language-culture interaction and on the study of linguistic and cultural concepts. Proverbs epitomize folk culture and wisdom and reveal the mentality and worldview of an ethnos. Research studies of particular interest focus on detecting the conceptual and semantic content of the notion of money and on the comprehensive presentation of the content of proverbs illustrating the concept of MONEY in Russian and English linguistic consciousness. The definitional analysis was used to interpret the notion of money. The method of the frame classification of proverbs found a possible identification of the main ‘meanings’ of proverbs, and the cognitive, linguistic and cultural approaches to the study of proverbs were used to describe the concept of money and to demonstrate a series of lexemes representing it. The study revealed the universal and specific features of this concept related to Russian and English attitudes towards money. The frame classification, which specifies the values and cultural knowledge of a national sphere of concepts, reflects the semantic space of proverbs relating to the concept under investigation. The results of the research will be useful to researchers involved in the study of cognitive semantics, paremiology and cross-linguistic/cultural studies.